Regulation of the human AP-endonuclease (APE1/Ref-1) expression by the tumor suppressor p53 in response to DNA damage - Zaky, Amira (Oxford University Press, 2008)
The human AP-endonuclease (APE1/Ref-1), an essential multifunctional protein, plays a central role in the repair of oxidative base damage via the DNA base excision repair (BER) pathway. The mammalian AP-endonuclease (APE1) overexpression is often observed in tumor cells, and confers resistance to various anticancer drugs; its downregulation sensitizes tumor cells to those agents via induction of apoptosis. Here we show that wild type (WT) but not mutant p53 negatively regulates APE1 expression. Time-dependent decrease was observed in APE1 mRNA and protein levels in the human colorectal cancer line HCT116 p53((+/+)), but not in the isogenic p53 null mutant after treatment with camptothecin, a DNA topoisomerase I inhibitor. Furthermore, ectopic expression of WTp53 in the p53 null cells significantly reduced both endogenous APE1 and APE1 promoter-dependent luciferase expression in a dose-dependent fashion. Chromatin immunoprecipitation assays revealed that endogenous p53 is bound to the APE1 promoter region that includes a Sp1 site. We show here that WTp53 interferes with Sp1 binding to the APE1 promoter, which provides a mechanism for the downregulation of APE1. Taken together, our results demonstrate that WTp53 is a negative regulator of APE1 expression, so that repression of APE1 by p53 could provide an additional pathway for p53-dependent induction of apoptosis in response to DNA damage.